Implementation of Educational Management Functions at SMP Muhammadiyah 06 Belawan - Feby Nur Indah Sari; Arif Hidayat Siregar; Zailani Zailani (Indonesian Journal of Education and Mathematical Science, 2023)
To build an organization including school organizations, management is very important. Notes some schools have slumped even to the point of bankruptcy because of bad management. This study aims to describe and analyze: (1) curriculum and learning management; (2) Student management; (3) Educator and education management personnel; (4) Facilities and infrastructure management; (5) Funding Management at SMP Muhammadiyah-06 Belawan.The research method uses a descriptive qualitative approach. Data collection techniques are carried out by interviews, documentation and observation. The results of this study are: 1. Curriculum management and learning at SMP Muhammadiyah-06 Belawan is carried out using the POAC management function. 2. Students management is going well. 3. The management of educators and educational staff has been carried out both based on management function. 4) Management of facilities and infrastructure in accordance with management standards. 5) Financing management is managed in an accountable manner